1996
DOI: 10.1007/s004310050555
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory control in children with Prader-Willi syndrome

Abstract: These findings indicate a primary disturbance of central respiratory control in patients with Prader-Willi syndrome which may be worsened by the development of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 15 publications
(21 reference statements)
3
48
0
1
Order By: Relevance
“…Her parents reported resolution of snoring and an improvement in her daytime sleepiness and behavior. Conversely, Schluter et al 20 described persistent irregular findings in 3 PWS children studied after adenotonsillectomy. All our patients showed preoperatively moderate to severe OSA and marked adenotonsillar hypertrophy; 2 patients were also obese.…”
Section: Discussionmentioning
confidence: 97%
“…Her parents reported resolution of snoring and an improvement in her daytime sleepiness and behavior. Conversely, Schluter et al 20 described persistent irregular findings in 3 PWS children studied after adenotonsillectomy. All our patients showed preoperatively moderate to severe OSA and marked adenotonsillar hypertrophy; 2 patients were also obese.…”
Section: Discussionmentioning
confidence: 97%
“…Although many aspects of PWS can be related to a basic defect in hypothalamic development, development of other systems is probably also compromised in PWS. Abnormal ventilatory responses to hyperoxia, hypoxia, and hypercapnia when awake and sleeping are noted in PWS patients Gozal et al, 1994;Schluter et al, 1997;Menendez, 1999). Furthermore, there are reports of sleep-related central and obstructive apnea (Clift et al, 1994;Wharton and Loechner, 1996;Manni et al, 2001;Nixon and Brouillette, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The major manifestations of PWS include neonatal hypotonia and failure to thrive, followed by childhood-onset developmental delay and obesity. Infants with PWS have significant respiratory abnormalities, including sleep-related central and obstructive apneas and reduced response to changes in oxygen and CO 2 levels Clift et al, 1994;Gozal et al, 1994;Wharton and Loechner, 1996;Schluter et al, 1997;Menendez, 1999;Manni et al, 2001;Nixon and Brouillette, 2002). A subset of genes in the region deleted in PWS, including the NDN gene encoding necdin, are active only on the paternally inherited allele and silenced by imprinting on the maternal allele (Nicholls, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated abnormal sleep patterns in patients with PWS that include hypoventilation, oxygen desaturation and sleep apnea [11–13, 3136]. In addition to ventilation control abnormalities, children with PWS have additional risk factors that predispose them to abnormal pulmonary function and respiratory responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in respiratory function are particularly common during sleep and are characterized by impaired ventilatory and arousal responses to hypoxia and hypercapnia in both adult and pediatric patients with PWS [5]. Sleep disordered breathing is one of the minor diagnostic criteria for PWS [10] and encompasses the entire spectrum of sleep-related disturbances from alveolar hypoventilation and hypoxemia to obstructive sleep apnea [11–13]. …”
Section: Introductionmentioning
confidence: 99%